Karakteristik koleksi plasma nutfah padi berdasarkan viabilitas dan vigor benih - Wira Hadianto; Lukman Hakim; Bakhtiar Bakhtiar (Jurnal Floratek, 2015)
Characteristics of Germplasm Collection Rice Based on Viability and Seed Vigor ABSTRACT. This research aims to investigate the characteristics of rice germplasm collection based on viability and seed vigor. The experimental design used in this research is completely randomized design (CRD) non factorial with three replications. Treatment rice genotypes consisted of 23 superior genotypes, 15 genotypes glutinous and 87 nonglutinous genotypes. This research was conducted at the Laboratory of Seed Science and Technology Faculty of Agriculture, Syiah Kuala University of Banda Aceh, from February to April 2014. The results showed that the genotype were highly significant effect on growth potential, rate of germination, vigor index, speed of growth, simultaneity grow and the time required to reach 50% germination (T50). The viability and vigor seed of superior genotypes best found in genotype IPB 3S and Kencana Bali. The best glutinous genotypes found in genotype Lekat Kumbob, Pulut Simanik and Pulut Merah. The best non-glutinous genotypes found in genotype Siputeh, Kuku Balam and Pade Sialek.